2000
DOI: 10.1002/j.2161-0045.2000.tb00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Readiness Assessment to Improve Career Services: A Cognitive Information‐Processing Approach

Abstract: This article begins with a review of the use of readiness assessment measures as a strategy for improving career services. A 5-step process model for readiness assessment is then proposed and current readiness measures are identified. Although considerable research has been conducted on career decision-making readiness and numerous measures have been developed, there has been limited literature available on the application of readiness assessment in selecting career interventions to meet specific client needs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 53 publications
2
135
0
4
Order By: Relevance
“…Increasingly differentiated levels of provision are delivered, according to individual client need (Sampson, 2005;Sampson, Peterson, Reardon, & Lenz, 2000), with an emphasis on making services more flexible and accessible. These changes in service delivery have sometimes occurred alongside other developments, like an emphasis on measurable outcomes and a dilution of professionalism within careers work (Mulvey, 2013).…”
Section: Policy At the Macro Levelmentioning
confidence: 99%
“…Increasingly differentiated levels of provision are delivered, according to individual client need (Sampson, 2005;Sampson, Peterson, Reardon, & Lenz, 2000), with an emphasis on making services more flexible and accessible. These changes in service delivery have sometimes occurred alongside other developments, like an emphasis on measurable outcomes and a dilution of professionalism within careers work (Mulvey, 2013).…”
Section: Policy At the Macro Levelmentioning
confidence: 99%
“…The counselor encouraged Alex to take the Career Thoughts Inventory (Sampson, Peterson, Lenz, Reardon, & Saunders, 1996). The screening aspect of this career readiness assessment in combination with clinical judgment helped the counselor to determine the level of support Alex needed (Sampson et al, 2000). Alex's readiness assessment results indicated that even though he is likely capable of making career decisions, his complex set of life circumstances place him in the category of needing moderate support (Sampson et al, 2000).…”
Section: March 2008 • Volume 56mentioning
confidence: 98%
“…Step 2: Preliminary Assessment The second step in implementing the CIP approach is the preliminary assessment, which integrates the initial interview with a readiness for career decision making (Peterson et al, 2002;Sampson, Peterson, Reardon, & Lenz, 2000). Although Alex touched on a myriad of potential counseling-related needs (e.g., war-related exposure to traumatic events, separation from wife), Litz and Orsillo (2004) recommended that counselors focus on the immediate needs and psychosocial functioning of the client first and address trauma exposure later in the counseling process.…”
Section: March 2008 • Volume 56mentioning
confidence: 99%
“…Readiness consists of two independent dimensions, capability and complexity (Sampson, Peterson, Reardon, & Lenz, 2000). The…”
Section: Conceptual Backgroundmentioning
confidence: 99%